2021
DOI: 10.1016/j.heliyon.2021.e06301
|View full text |Cite
|
Sign up to set email alerts
|

How brand attitude, brand quality, and brand value affect Thai canned tuna consumer brand loyalty

Abstract: As one of the world's most valuable fish, Tuna can either be found in inexpensive tins on grocery store shelves or on high-end auction blocks destined for Japanese sashimi and sushi restaurants. Moreover, Thailand is reported to be the world's largest exporter of prepared or preserved tuna, which in 2019 contributed an estimated $2.5 billion to Thailand's exports. However, brand research is very limited for canned tuna, especially when it comes to product packaging cues, and how packaging affects a consumer's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 36 publications
3
24
0
3
Order By: Relevance
“…The Human Ethics Committee from our research university was notified and consulted before meeting with experts concerning the questionnaire's design and the questionnaire's pre-test. Along with the committee's approval, we obtained an informed consent form from each survey participant which stated that each participant's anonymity was ensured (Chuenban et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Human Ethics Committee from our research university was notified and consulted before meeting with experts concerning the questionnaire's design and the questionnaire's pre-test. Along with the committee's approval, we obtained an informed consent form from each survey participant which stated that each participant's anonymity was ensured (Chuenban et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…However, before the questionnaire distribution and shortly after its conceptualisation, seven experts in business computer and digital technology studies reviewed each of the questionnaire's items and gave their assessment of the survey instrument's content quality. Numerous studies, such as Chuenban et al (2021), have suggested that the index of item-objective congruency (IOC) is a useful numerical tool in the experts' assessment process which includes 1) its relevance to the questionnaire's aim, 2) its clarity, 3) its comprehensiveness and completeness and, finally, 4) its significance and meaningfulness for each item.…”
Section: Reliability and Validity Assessmentmentioning
confidence: 99%
“…Section 4 was related to the importance of AT skills, and finally, Section 5 had five items relating to KA skills. The interpretation of each individual's opinions for each item used a scale where 4.51-5.00 indicated 'strongly agree', 3.51-4.50 indicated 'high agreement', 2.51-3.50 indicated 'moderate agreement', 1.51-2.50 indicated 'little agreement' and 1.00-1.50 indicated 'minimal agreement' (Chuenban et al, 2021). Finally, Section 3 allowed for the input of suggestions and recommendations.…”
Section: Research Instrumentmentioning
confidence: 99%
“…Brand loyalty include a commitment to a brand that originates in satisfaction with the brand, a reference to the brand, and the consistency of the brand (Chuenban, Sornsaruht, &Pimdee, 2021). The comfort is awakened by a feeling that arises as a result of the minimum or absence of certain disturbances.…”
Section: Brand Loyaltymentioning
confidence: 99%